1980
DOI: 10.1128/aac.17.4.669
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pharmacokinetic Evaluation of Parenteral Cefoxitin in Infants and Children

Abstract: Thirty-two infants and children ranging in age from 3 to 151 months (mean, 26 months) were treated with parenteral cefoxitin (150 mg/kg per day). Ten patients with isolates of Haemophilus influenzae (six with cellulitis, two with arthritis, and two with mastoiditis), four with Staphylococcus aureus (one with lymphadenitis, one with septicemia, and two with abscess), and three patients with Streptococcus pneumoniae (one each with cellulitis, abscess, and arthritis), were clinically and bacteriologically cured b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
1

Year Published

1982
1982
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
0
7
1
Order By: Relevance
“…The dosage used in this study of 75 mg of cefoxitin per kg every 6 hours was larger than those previously reported (2,8). However, the half-lives and volumes of distribution were comparable with those previously reported (2) for a smaller dosage (37.5 mg/kg) every 6 hours.…”
contrasting
confidence: 41%
See 2 more Smart Citations
“…The dosage used in this study of 75 mg of cefoxitin per kg every 6 hours was larger than those previously reported (2,8). However, the half-lives and volumes of distribution were comparable with those previously reported (2) for a smaller dosage (37.5 mg/kg) every 6 hours.…”
contrasting
confidence: 41%
“…Cefoxitin is a semisynthetic cefamycin, active in vitro against common meningeal pathogens such as Neisseria meningitidis, Streptococcus pneumoniae, and ampicillin-susceptible and -resistant strains of Haemophilus influenzae type b (1,2,6,8,14,17). The results of clinical trials in adults (6,12,13) and children (2,8) have shown that this drug is safe and effective against infections with S. pneumoniae and H. influenzae b outside the central nervous system.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the apparent serum half-life is shorter in children 2-11 years of age than in adults and approaches 3 h in premature infants and neonates (WARREN et al 1979;Roos et al 1979;MARGET et al 1979;WILKINSON et al 1979;FELDMAN et al 1980;OLEGARD et al 1979). BUCHANAN et al (1980) noted no large differences in the disposition of cefoxitin in children during kwashiorkor and after the disease was cured.…”
Section: Cefoxitinmentioning
confidence: 96%
“…1980 Feldman et al [57] Prospective cohort study 32 children Cellulitis, abscess, arthritis, bacteremia 89% 1996 Stiglmayer et al [52] Randomized controlled trial 76 Pelvic inflammatory disease 79%…”
Section: Esbl Infectionsmentioning
confidence: 99%